Debating the responsibility to protect: inconsistencies between Libya and Bahrein - Alonso García, Serena (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2021)
This paper analyzes the doctrine of the responsibility to protect, studying its essential characteristics, as well as the different dimensions that comprise it, and the usefulness of each one of them. In addition, it carries out a detailed analysis of its application based on two case studies, in which the weaknesses of the doctrine are analyzed, as it has been configured up to the present, with the purpose of exposing those points where it can be improved. Despite these proposals of improvement, this paper aims to encourage the promotion and development of a doctrine that, if used correctly, can help to protect civilian populations from heinous crimes.
Keywords: Libyan conflict; ICISS report; humanitarian interventions; sovereignty and human rights; responsibility to protect